Science comics : skyscrapers - Kerschbaum, John. (2019)
Join a pair of superheroes as they uncover the secrets of skyscrapers, from the great Egyptians pyramids to the world$1 (Bs tallest building. Read along and learn how skyscrapers are a bold combination of applied physics, ingenuity, and a lot of hard work!s
9-13